Multifunctional Fiber‐Enabled Intelligent Health Agents. Issue 52 (12th July 2022) - Chen, Min; Li, Pan; Wang, Rui; Xiang, Yuanzhuo; Huang, Zhiheng; Yu, Qiao; He, Muyao; Liu, Jia; Wang, Jiaxi; Su, Minyu; Zhang, Manni; Jian, Aijia; et al.
Abstract: The application of wearable devices is promoting the development toward digitization and intelligence in the field of health. However, the current smart devices centered on human health have disadvantages such as weak perception, high interference degree, and unfriendly interaction. Here, an intelligent health agent based on multifunctional fibers, with the characteristics of autonomy, activeness, intelligence, and perceptibility enabling health services, is proposed. According to the requirements for healthcare in the medical field and daily life, four major aspects driven by intelligent agents, including health monitoring, therapy, protection, and minimally invasive surgery, are summarized from the perspectives of materials science, medicine, and computer science. The function of intelligent health agents is realized through multifunctional fibers as sensing units and artificial intelligence technology as a cognitive engine. The structure, characteristics, and performance of fibers and analysis systems and algorithms are reviewed, while discussing future challenges and opportunities in healthcare and medicine. Finally, based on the above four aspects, future scenarios related to health protection of a person's life are presented. Intelligent health agents will have the potential to accelerate the realization of precision medicine and active health. Abstract : A multifunctional fiber‐enabled intelligent health agent with characteristics of autonomy, activeness, intelligence, and perceptibility, enabling health services, is proposed. Four major aspects driven by intelligent agents are summarized from the perspectives of materials science, medicine, and computer science. The agent is realized through multifunctional fibers as sensing units and artificial intelligence technology as a cognitive engine.